GIS for power distribution network: A case study of Karachi, Pakistan - ﻿Syed Nawaz-ul-Huda,; Burke, ﻿Farkhunda; ﻿Muhammad Azam,; ﻿Shazia Naz, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
﻿Due to rapid population increase and accelerated daily energy demand, electricity theft has become one of the common crimes in developing countries. Load shedding is observed not only for electricity but also for natural gas leading to further revenue losses for the state. The energy sector in Pakistan has long been facing serious problems of electricity generation and distribution. The aim of this paper is to present a case for a GIS modeling for Spatial Electricity Management System in Karachi so as to help circumvent the recurrent problems of electricity theft and mal-distribution in the city.